2006
DOI: 10.1116/1.2362783
|View full text |Cite
|
Sign up to set email alerts
|

Mobility and charge density tuning in double δ-doped pseudomorphic high-electron-mobility transistors grown by metal organic chemical vapor deposition

Abstract: In this article, the authors present mobility and charge density tuning for metal organic chemical vapor deposition (MOCVD)-grown double δ-doped pseudomorphic high-electron-mobility transistors (PHEMTs). Good epitaxial wafers were obtained by MOCVD as indicated by uniform and abrupt interfaces seen in measurements taken using a transmission electron microscope and two pronounced Si-δ-doped peaks in the secondary ion mass spectrometry analysis. The 1-μm-gate-length PHEMT device exhibited good dc performance wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The strain effect of GaAs/InGaAs heterostructures on the electron mobility has been analysed [14][15][16][17][18][19][20]. Low temperature mobility of 2DEG in InGaAs/AlGaAs modulation-doped by acceptors and donors has been studied for its use in microwave transistors [21].…”
Section: Introductionmentioning
confidence: 99%
“…The strain effect of GaAs/InGaAs heterostructures on the electron mobility has been analysed [14][15][16][17][18][19][20]. Low temperature mobility of 2DEG in InGaAs/AlGaAs modulation-doped by acceptors and donors has been studied for its use in microwave transistors [21].…”
Section: Introductionmentioning
confidence: 99%
“…The InGaAs based pseudomorphic high electron mobility transistors (p-HEMTs) support high power gain, low noise and exceptional cut-off frequency and also exhibit excellent logic characteristics [5][6][7]. The p-HEMTs with delta-doped channels show good performance in high speed applications [8][9][10]. Thin-channel p-HEMTs have been explored to have excellent current drive and sub-threshold swing [7,8,11].…”
Section: Introductionmentioning
confidence: 99%
“…This provides an additional degree of freedom to tailor the band structure of the material [14]. A number of works have been done on the study of the electron mobility μ of GaAs/InGaAs based p-HEMT structures [10][11][12][13][15][16][17][18][19][20]. It has been shown that in a multi-subband occupied quantum well system; μ substantially depends on the intersubband effects [17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Much effort has been made to study the enhancement of the electron mobility in the InGaAs-based pseudomorphic channels by employing different structure geometry and doping profiles. [10][11][12][13][14][15] A double quantum well is an interesting system because of the occurrence of tunneling coupling in addition to the quantum confinement of the carriers. 16,17) When two separate wells are brought closer to each other, their subband wave functions overlap through the central barrier, leading to the splitting of the subband energy levels.…”
Section: Introductionmentioning
confidence: 99%